Temperature study and genome analysis of marine Pseudoalteromonas sp. - Moore, Opal E (East Carolina University, 2023)
Aluminum is a metal prized for its versatility. In the marine environment, aluminum is used in a variety of applications including ship building and oceanic equipment. However, constant seawater exposure corrodes aluminum and allows for biofouling, or the accumulation of organisms on the surface, which can damage the integrity of marine structures over time. To discourage this, man-made coatings are often applied, but serve as a source of environmental concern due to toxic chemical leach. Marine Pseudoalteromonas sp., isolated from an aluminum coupon submerged in the Pamlico River, is a bacterium thought to form uniquely protective biofilms which could prevent degradation and excrete anti-biofouling compounds. This property would make the bacteria a potential source for a natural aluminum-preserving coating in situ. To determine the optimal conditions for growth, the Pseudoalteromonas sp. was measured over twenty-four hours using an optical density plate reader at temperatures representative of a variety of marine environments; 22℃, 25℃, 30℃, and 35℃. DNA from the isolate was extracted and sequenced using fluorescence-based detection and PCR amplification to better understand the metabolism, anti-biofouling properties, and toxicity resistance unique to the isolate. The resulting DNA contigs were then analyzed into an annotated genome with Rapid Annotation using Subsystem Technology (RAST). When compared to isolates from the same source, the Pseudoalteromonas sp. displayed fewer iron-regulatory genes, more water-soluble nutrient metabolism genes, and a tendency to secrete antibacterial peptides (ABPs). Being able to recognize the environments associated with Pseudoalteromonas sp., and understanding on a genomic level what sets it apart, we can begin to answer the questions posed for research in addition to facilitating methods for preserving and prolonging the existence of current and future marine structures in ways that are environmentally sound.
Keywords: Pseudoalteromonas: temperature study; genome analysis; microbiology